2021
DOI: 10.31635/ccschem.020.202000235
|View full text |Cite
|
Sign up to set email alerts
|

Nickel- and Brønsted Acid-Catalyzed Redox-Neutral Coupling of 1,3-Dienes and Aldehydes for Synthesis of Dienols

Abstract: Dienols are important structural motifs in organic molecules, but most of the traditional synthetic methods required multistep prefunctionalization of substrates, leading to stoichiometric waste and low atom economy. Herein, we report a redox-neutral coupling of simple 1,3-dienes and aldehydes via nickel and Brønsted acid dual catalysis, providing a highly atom-economical and by-product-free route to various dienols with up to 94% yield and up to 50∶1 EE/EZ ratio. The use of 2-isopropoxyphenol as a Brønsted ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Inspired by the previous observations that compounds bearing active protons (e.g. TsNH 2 , phenol) could promote opening of the fivemembered nickellacycle intermediate via protonation 50,54,[62][63][64] , as well as studies of transmetallation on boronates [65][66][67][68][69] , we proposed that a boronate facilitates exchange of the sulfonamidyl group on the nickel, leading to rapid opening of the nickellacycle (a to b in Fig. 1c).…”
Section: Resultsmentioning
confidence: 90%
“…Inspired by the previous observations that compounds bearing active protons (e.g. TsNH 2 , phenol) could promote opening of the fivemembered nickellacycle intermediate via protonation 50,54,[62][63][64] , as well as studies of transmetallation on boronates [65][66][67][68][69] , we proposed that a boronate facilitates exchange of the sulfonamidyl group on the nickel, leading to rapid opening of the nickellacycle (a to b in Fig. 1c).…”
Section: Resultsmentioning
confidence: 90%
“…On the basis of the experimental results and the previous literature, 10,11 a plausible catalytic cycle is proposed in Scheme 4. First, the oxidative addition of the in situ generated Pd(0) to the proximal C–C bond of ACPs 1 generates a cyclic Pd( ii ) complex I .…”
Section: Resultsmentioning
confidence: 82%
“…Recently, dual catalysis by transition metal and a Brønsted acid has been proven to be a powerful strategy for redox-neutral coupling of alkenes and carbonyl compounds. 11 Thus, a series of Brønsted acids were tested in this reaction. Pleasingly, both the reactivity and the selectivity were improved with the addition of N -Boc-L- tert -Leucine (Boc-L-Tle-OH).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, Ye and co-workers demonstrated the effective use of a catalytic amount of Brønsted acid, specifically PhB(OH) 2 , in hydroalkenylation of aldehydes with styrene and related derivatives (Scheme 50). 124,125 Both the alcoholic solvent and PhB(OH) 2 were crucial to the reaction's success, leading the authors to suggest that a coordinated complex involving PhB(OH) 2 and ethanol might serve as a superior acid catalyst. Furthermore, Han and Liu 126 investigated the reaction mechanisms of nickel-catalysed hydroalkenylation of aldehydes with styrenes using DFT calculations.…”
Section: Catalytic Transformations Of Simple Alkenes Including Ethyle...mentioning
confidence: 99%